Ethical Decision Making: Increasing your chances to make better decisions - Robert F. Hachiya (The Advocate, 2014)
Ethical decision-making is an important skill for leaders that can be acquired and improved with experience. Successful leaders consistently make right decisions and inspire confidence in others. While many fields include formal ethics classes as a part of their required curriculum, only recently has the field of education included formalized ethics training for principals. This article provides guidance and advice for those seeking to increase the likelihood they will make better decisions each day.